A time series study of the association between extreme temperature and ozone on varicella incidence - Juan Zhang; Binhao Wang; Zixuan Li; Wanze Zhang; Siyao Yan; Qiaoling Geng; Xian Guo; Zitong Zhao; Jianning Cai; Lijuan Liu; Xiaolin Zhang (Scientific Reports)
Abstract This study aimed to discuss the effects of extreme temperatures and ozone on the incidence of varicella in Shijiazhuang City from 2014 to 2022, which provides new ideas for preventing public health events. METHODS We collected varicella cases in Shijiazhuang, China, from 2014 to 2022 and evaluated the relationship between temperature extremes and ozone on varicella incidence by building distributional lag nonlinear models. The analysis was stratified by age and sex, with 19,188 varicella cases reported. A nonlinear “J”-shaped relationship emerged between mean daily temperature and varicella incidence, where colder temperatures heightened risk, while hotter ones reduced it, particularly affecting females and adolescents. Additionally, ozone concentration displayed an “S”-shaped correlation, with low levels posing a risk and high levels protective against varicella, notably among females and adults. Our study results show a significant correlation between extreme temperatures and ozone concentrations on varicella incidence, and this study may help prevention and control authorities to create timely warnings of high-risk outbreaks, and assist the public in responding to varicella outbreaks.